Chilean public attitudes towards beef production systems. - Valentina Mansky de la Fuente; Daniel Enriquez-Hidalgo; Dayane Lemos Teixeira; Rafael Larrain; Maria Jose Hötzel (PLoS ONE)
Much is discussed about the characteristics, efficiency, and externalities of indoor housing and pasture-based beef production systems, but little is known about how these features influence public attitudes towards beef production. This study aimed to explore Chilean citizens' attitudes towards beef production systems and their underlying reasons. Citizens (n = 1,084) were recruited to participate in a survey and given information about one beef production system: indoor housing, continuous grazing or regenerative grazing. Participants had more favourable attitudes (from 1 = most negative attitudes to 5 = most positive attitudes) towards pasture-based systems (regenerative grazing = 2.94; continuous grazing = 2.83) than towards indoor housing (1.94), mainly due to concerns with animal welfare and environmental impacts. Productivity was not as important as the other sustainability aspects for participants as they were not willing to do that trade-off. Support for beef production may benefit if production systems adopt characteristics that are perceived by the public as positive for the environment and animal welfare.